"I Remember the Mental Chaos While They Tried To Seal the Well and Clean Up the Oil Spill – How Much Fear and Uncertainty Everyone Felt": An interview with Marylee and Michael Orr, Louisiana Environmental Action Network. (November 2018) - Sullivan, John; Rosenberg, Beth
In this interview, Marylee Orr and her son, Michael Orr, of the Louisiana Environmental Action Network (Baton Rouge, LA) recall the massive trauma among fishing families (including those whose boats were used in the clean-up effort) caused by the Deep Water Horizon spill, the state and federal closures of fishing grounds, and the moratorium on oil exploration and production activity during the clean-up efforts. They recount the history of their organization's vision and growth, their role in regional environmental justice efforts, and outline how they developed an approach to rapid response community empowerment based on colearning, respect, consensus, and action—a vision that parallels the work of Paulo Freire and the practice values of community-based participatory research. They discuss the collaborative seafood sampling site map and toxicology primer they built and archived as a key community partner of the Gulf Coast Health Alliance: Health Risks Related to the Macondo Spill Project.